Implications of the ‘Open-Door Church’ Concept in the Apostolic Exhortation Evangelii Gaudium for the Pastoral Work of the Church in Indonesia - Benediktus Denar; Jean Loustar Jewadut; Asni Asmawati (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2025)
This article aims to explain the concept of the “Open-Door Church” in the apostolic exhortation Evangelii Gaudium and to apply in the pastoral work of the Church in Indonesia. This study employs a qualitative method, focusing on in-depth literature review complemented by systematic content analysis of primary and secondary sources. The primary document studied is Evangelii Gaudium to gain a comprehensive understanding the concept of the “Open-Door Church”. Based on an in-depth examination of the document, the “Open-Door Church” is defined as the Church's effort to move beyond the comfort zone of liturgical-centered pastoralism, a Church ready to welcome all people of good will, a Church that prioritizes service to the poor, a Church that continually renews itself internally, and a Church that respects the culture of the community. The “Open-Door Church” demands pastoral work that is sensitive to the signs of the times, focuses on diakonia for the poor, and prioritizes intergenerational evangelization for those of different faiths and the poor. By becoming a “Open-Door Church”, the synodal aspect of the Church becomes stronger.